The Use of Assistance Computer Word Processor To Teach Writing Skill For EFL learners - Azizaturrohmi, Zulfa (VELES Voices of English Language Education Society, 2019)
This study aimed at determining the effectivenes of Assistance of Computer Word Processor to teach writitng skill for the eleventh grade students of MA Muallimat NW Pancor in the school year 2017-2018. The purposed of the research were 1) to find out whether or not Assistance Computer Word Processor is effective in teaching writing for the eleventh grade students of senior high school in the school year 2017-2018 and 2) to know how effective Assistance Computer Word Processor is in teaching writing skill for the eleventh grade students of senior high school in the school year 2017-2018. This research was a pre-experimental research. The population was 94 students and and sample was 30 students. The instrument used in this resarch was essay test. The researcher gave a pre test in the fisrt meeting, treatment, and post test in the last meeting. The result of mean score of pre-test was (30.93) and the mean score in post-test  was (69.06). After analyzing through the data use SPSS, the researcher found that there was significant difference between the mean score before and and after treatment, t(df = 29) =48.42 at p= 0.000. After conducted the research, researcher found that using Assistance Computer Word Processor was effective in teaching writing skill for eleventh grade students of MA Muallimat NW Pancor. There is no doubt that the Word Processor was helpful tool in improving students writing skill.